Ultrasound Measurement of Vascular Distensibility Based on Edge Detection and Speckle Tracking Using Ultrasound DICOM Data. Issue 1 (10th August 2021) - Funes-Lora, Miguel Angel; Thelen, Brian J.; Shih, Albert J.; Hamilton, James; Rajaram, Nirmala; Lyu, Jingxuan; Zheng, Yihao; Morgan, Timothy; Weitzel, William F.
Abstract : This study presents an edge detection and speckle tracking (EDST) based algorithm to calculate distensibility as percentage of change of vessel diameter during cardiac cycles. Canny edge detector, Vandermonde matrix representation, Kanade Lucas Tomasi algorithm with pyramidal segmentation, and penalized least squares technique identifies the vessel lumen edge, track the vessel diameter, detrend the signal and find peaks and valleys when the vessel is fully distended or contracted. An upper extremity artery from 10 patients underwent an ultrasound examination as part of preoperative evaluation before arteriovenous fistula surgery. Three studies were performed to evaluate EDST with automatic peak and valley selection versus manual speckle selection of expert users using manual peak and valley selection. Results demonstrate the effectiveness of the proposed methodology, to obtain comparable results as those obtained by expert-users, and considerably reducing the variability associated with external factors such as excessive motion, fluctuations in stroke volume, beat-to-beat blood pressure changes, breathing cycles, and arm-transducer pressure.